"Turn-on" fluorescence sensing of volatile organic compounds using a 4-amino-1,8-naphthalimide Tröger's base functionalised triazine organic polymer - Watson, Graeme; Schmitt, Wolfgang; Gunnlaugsson, Thorfinnur (My University, 2019)
The 4-amino-1,8-naphthalimide Tröger's base functionalized triazine covalent organic polymer TB-TZ-COP was synthesised and employed as a “turn-on” fluorescent and a colorimetric sensor for the discriminative sensing of volatile organic compounds; the TB-TZ-COP displaying the largest fluorescent enhancement and high sensitivity for 1,4-dioxane, a harmful environmental pollutant classified as a Group 2B carcinogen.
PUBLISHED